Encountering the west Christianity and the global cultural process : The african dimension - Sanneh, Lamin O. (London Marshall Pickering, 1993)
Takes as its subject the emergence of a distinctive Third-World - particularly African - Christianity, as it uncouples itself from the Western cultural package in which Christianity was introduced there. Today the focus is reversed - non-Western nations have much to teach the West about the Gospel.
Keywords: Christianity and culture. Missions. Missions -- Africa. Christianity and other religions. Christianity and other religions -- Islam. Islam -- Relations -- Christianity. Religious pluralism -- Christianity. Africa -- Civilization -- Western influences. Christianity Christianity and culture Christianity and other religions Civilization -- Western influences Interfaith relations Islam Missions Religious pluralism -- Christianity Africa